PENERAPAN METODE INKUIRI DENGAN PENDEKATAN TANOSHII JUGYOU UNTUK MEMPERBAIKI KONSEP OPERASI BILANGAN - Dyah Ayu Sulistyaning Cipta (Program Studi Pendidikan Matematika, 2019)
The purpose of this study was to describe the design of inquiry learning methods with Tanoshii Jugyou's approach so that students who take the SD Mathematics Study course understand the concept of operations on integers and fractions. This research is a qualitative research that illustrates how the learning of inquiry methods with Tanoshii Jugyou approach is applied in the classroom. The results of the study concluded that the learning design of inquiry methods with Tanoshii Jugyou's approach to the concept of operations on integers and fractions is: 1) orientation to create a more responsive learning atmosphere, 2) formulating problems to bring students to a problem that must be solved, 3) making hypothesis, 4) collect data to capture the required information which will then be used to test hypotheses that have been proposed, 5) test the hypothesis. In testing this hypothesis lies the emphasis of this learning so that students can truly understand the concept of operations on integers and fractions. All learning activities are carried out by making the classroom atmosphere very pleasant. Students are welcome to issue their creative ideas without the slightest fear.